Localization and pair breaking parameter in superconducting molybdenum nitride thin films. (10th November 2016) - Tsuneoka, Takuya; Makise, Kazumasa; Maeda, Sho; Shinozaki, Bunju; Ichikawa, Fusao
Abstract: We have investigated the superconductor-insulator transition in molybdenum nitride films prepared by deposition onto MgO substrates. It is indicated that the T c depression from ≈ 6.6 K for thick films with increase of the normal state sheet resistance R sq N was well explained by the Finkel'stein formula from the localization theory. Present analysis suggests that the superconducting-insulator transition occurs at a critical sheet resistance R c ≈ 2 kΩ . It is found that the R sq ( T ) above R c shows different characteristics of R sq ( T ) = R sq, 0 − A ln T and R s q ( T ) ∝ exp [ ( T 0 / T ) 1 / 2 ] in the regions R c < R sq N < R Q = h / 4 e 2 ≈ 6.45 kΩ and R sq N > R Q, respectively, where R sq, 0 is the classical residual resistance and A is a constant. The excess conductance σ ′ ( T ) due to thermal fluctuation has been analyzed by the sum of the Aslamazov–Larkin and Maki–Thompson correction terms with use of the pair breaking parameter δ in the latter term. The sum agrees well with the data, although the experimental results of the R sq N dependence of δ, that is, δ ∝ ( R sq N ) ≈ 1.7 shows the disagreement with a linear relation δ ∝ ( R sq N ) derived from the localization theory.